2021
DOI: 10.1155/2021/5888432
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] ROS Signaling‐Mediated Novel Biological Targets: Brf1 and RNA Pol III Genes

Abstract: Biomolecule metabolism produces ROS (reactive oxygen species) under physiological and pathophysiological conditions. Dietary factors (alcohol) and carcinogens (EGF, DEN, and MNNG) also induce the release of ROS. ROS often causes cell stress and tissue injury, eventually resulting in disorders or diseases of the body through different signaling pathways. Normal metabolism of protein is critically important to maintain cellular function and body health. Brf1 (transcript factor II B-related factor 1) and its targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The anticancer effect of zinc was mainly attributed to its antioxidant properties. Under homeostatic conditions, the body produced reactive oxygen species (ROS), which were involved in many biological processes (cell differentiation, apoptosis) ( 29 , 30 ). Due to the high metabolic demand of tumors, tumor tissues produced large amounts of ROS, which promoted tumor growth by causing DNA damage and inducing gene mutations ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anticancer effect of zinc was mainly attributed to its antioxidant properties. Under homeostatic conditions, the body produced reactive oxygen species (ROS), which were involved in many biological processes (cell differentiation, apoptosis) ( 29 , 30 ). Due to the high metabolic demand of tumors, tumor tissues produced large amounts of ROS, which promoted tumor growth by causing DNA damage and inducing gene mutations ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer effect of zinc was mainly attributed to its antioxidant properties. Under homeostatic conditions, the body produced reactive oxygen species (ROS), which were involved in many biological processes (cell differentiation, apoptosis) (29,30). 1 , the total SNPs after the screen using the p-value, physical distance (kb > 10,000), and linkage disequilibrium (R 2 < 0.001); nSNP 2 , the total SNPs after the removal of incompatible, palindromic, and outlier SNPs; P (mr_presso): The P for the testing of outlier SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%